2021
DOI: 10.1002/prp2.773
|View full text |Cite
|
Sign up to set email alerts
|

The importance of collaboratively designing pharmacology education programs

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…15 However, currently, the instruction of molecular pharmacology primarily relies on theoretical knowledge and lacks a comprehensive molecular pharmacology is a cutting-edge interdisciplinary subject, and a proper experimental training system is necessary for students to master the research capability that does good to their future careers. 16 The experimental framework employed in this thesis represents a scholarly and pedagogical amalgamation of theoretical instruction in molecular pharmacology and scientific progress, with the objective of enhancing students' understanding of classical theories of molecular pharmacology and improve their experimental skills and scientific thinking.…”
Section: Discussionmentioning
confidence: 99%
“…15 However, currently, the instruction of molecular pharmacology primarily relies on theoretical knowledge and lacks a comprehensive molecular pharmacology is a cutting-edge interdisciplinary subject, and a proper experimental training system is necessary for students to master the research capability that does good to their future careers. 16 The experimental framework employed in this thesis represents a scholarly and pedagogical amalgamation of theoretical instruction in molecular pharmacology and scientific progress, with the objective of enhancing students' understanding of classical theories of molecular pharmacology and improve their experimental skills and scientific thinking.…”
Section: Discussionmentioning
confidence: 99%
“…They exemplify the factor of "Pharmacology as an indispensable course in medical education". Pharmacology is a core component of medical education because it is essential for the safe and effective use of medications, which are a cornerstone of modern medicine (1,3). It has been shown that the prescribing/pharmacology course in undergraduate medical education is among the courses that require more focus and has been one of the more demanded courses by students.…”
Section: Discussionmentioning
confidence: 99%
“…Prescribing errors can cause serious harm such as disability, hospitalization, and death (2). Learning pharmacology is important for improving public health in terms of preventing medicationinduced adverse events and drug-drug interactions (3). Although pharmacology education is an essential component of medical education, it is an intimidating course in medical education programs (4) because the sheer volume of information and complexity of pharmacology can be daunting.…”
Section: Introductionmentioning
confidence: 99%